مبدأالآلام التي لا مبرر لها في الفقه الإسلامي والقانون الدولي الإنساني - حسيني, فضيل (University of eloued جامعة الوادي, 2022)
"الملخص: تهدف هذه الدراسة إلى التعرف على مبدأ من المبادئ الأساسية التي يعتمد عليها في تنظيم سير العمــليات العدائية أثناء النّزاعات المسلّحـــــــة وحمــــــاية ضحايا هذه النّزاعـــات، ألا هو "" مبدأ الآلام التي لا مبرر لها "" من منظور الفقه الإسلامي والقانون الدولي الإنساني. وترمي الدراسة إلى معالجة الإشكالية التالية: كيف يساهم مبدّأ الآلام التي لا مبرر لها في الحد من الآثار السلبية للنزاعات المسلحة بتقييد اختيار وسائل وأساليب القتال وفقا لقواعد الفقه الإسلامي والقانون الدولي الإنساني ؟ وخلصت الدراسة إلى أن ّإقرار مبدأ الآلام التي لا مبرر لها في الفقه الإسلامي غايته تعبدية، بالإضافة إلى أن الحرب ليست بهذا الإطلاق فلا يجوز أن تتجاوز الأهداف المتوخاة منها تحت أي ذريعة كانت، ولابد من تفادي كلّ فعل من شأنه أن يسبب معاناة مفرطة وآلام لا مبرر لها يمكن أن تلحق بالمدنيين أو الأعيان المدنية والبيئة الطبيعية. ""Summary: This study aims to identify one of the basic principles on which it depends in regulating the conduct of hostilities during armed conflicts and protecting the victims of these conflicts, which is the “principle of unjustified suffering” from the perspective of Islamic jurisprudence and international humanitarian law. The study aims to address the following problem: How does the principle of unjustified pain contribute to limiting the negative effects of armed conflicts by restricting the choice of means and methods of combat in accordance with the rules of Islamic jurisprudence and international humanitarian law? The study concluded that the adoption of the principle of unjustified pain in Islamic jurisprudence has a devotional goal, in addition to the fact that war is not at all that it is not permissible to exceed the goals envisaged by it under any pretext, and every action that would cause excessive suffering and unjustified pain must be avoided. It can inflict civilians, civilian objects and the natural environment. "
شريعة وقانون
Keywords: الآلام . الفقه الإسلامي. القانون لدولي الإنساني.; unexplained pain. Islamic Fiqh. International humanitarian law.